Experimental study on initiation and propagation behavior of propane/oxygen/nitrogen detonation wave. (1st June 2021) - Liu, Shizheng; Chen, Xiang; Zhao, Ningbo; Zheng, Hongtao; Jia, Xiongbin
Highlights: The detonation cell sizes of C3 H8 /O2 /N2 are measured by experimental. Increasing nitrogen causes the cell irregular and makes its sharp angle smooth. The cell size reaches the minimum of 6.957 mm at equivalence ratio 1.2. The DDT distances under different equivalence ratios are compared. Abstract: In this experiment, detonation cell sizes of propane/oxygen/nitrogen under different initial conditions was measured, including the ratio of nitrogen to oxidant, equivalence ratio and initial pressure. The influences of different conditions on the transition distance from deflagration to detonation and detonation velocity were analyzed. The results indicate that increasing the ratio of nitrogen to oxidant will increase the size of detonation cell and make its structure irregular. More nitrogen will reduce the detonation velocity. Besides, the relationship between the size of detonation cell and the equivalence ratio displays a U-shaped curve. When the equivalence ratio is 1.2, the size of detonation cell reaches the minimum value of 6.957 mm. In addition, the experimental data shows that increasing initial pressure will increase the concentrations of fuel and oxidant, accelerate the molecular movement inside the tube, and eventually accelerate the detonation velocity. The increase of initial pressure will increase the collision frequency between transverse waves and incident shock waves, and finally reduce the size of detonation cell.